1998
DOI: 10.1172/jci1089
|View full text |Cite
|
Sign up to set email alerts
|

The HPV-activating cellular transcription factor Brn-3a is overexpressed in CIN3 cervical lesions.

Abstract: The cervical cellular transcription factors Brn-3a and Brn-3b have antagonistic effects on transcription of the human papilloma virus types 16 and 18 E6 and E7 oncogenes, with Brn-3a activating expression and Brn-3b repressing it. We therefore measured expression of Brn-3a and Brn-3b mRNAs in biopsies from 16 women with no detectable cervical abnormality, and in 14 women with cervical intraepithelial neoplasia grade 3 (CIN3) lesions. Although the mean level of Brn-3b expression was similar in both groups, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…To quantitate the level of Brn-3a and Brn-3b mRNAs we used a reverse transcriptase/polymerase chain reaction (RT ± PCR) assay which we have previously used to reliably quantitate these mRNAs in small amounts of clinical and other material (Ndisang et al, 1998;Smith and Latchman, 1996). This assay was used to compare the levels of Brn-3a and Brn-3b mRNAs in normal breast tissue or benign breast tumour material with that obtained from malignant breast tumours from pre-or post-menopausal women.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To quantitate the level of Brn-3a and Brn-3b mRNAs we used a reverse transcriptase/polymerase chain reaction (RT ± PCR) assay which we have previously used to reliably quantitate these mRNAs in small amounts of clinical and other material (Ndisang et al, 1998;Smith and Latchman, 1996). This assay was used to compare the levels of Brn-3a and Brn-3b mRNAs in normal breast tissue or benign breast tumour material with that obtained from malignant breast tumours from pre-or post-menopausal women.…”
Section: Resultsmentioning
confidence: 99%
“…Membranes were exposed to ®lms, (Eastman Kodak Co., Rochester, NY, USA) and the subsequent autoradiographs were then analysed using a densitometer (Bio-Rad Laboratories, Hercules, CA, USA). We have previously shown that this blotting procedure, in conjunction with the RT ± PCR conditions used, allows accurate quanti®cation of the Brn-3a and Brn-3b mRNAs relative to the constitutively expressed cyclophilin mRNA (Lillycrop et al, 1992;Ndisang et al, 1998;Morris et al, 1994).…”
Section: Normal and Breast Cancer Samplesmentioning
confidence: 99%
See 3 more Smart Citations